Clinical Application of TERT Promoter Mutations in Urothelial Carcinoma - Hayashi, Yujiro; Fujita, Kazutoshi; Netto, George J.; Nonomura, Norio (Frontiers in Oncology, 2021)
Urothelial carcinoma (UC) is a common urological malignancy with a high rate of disease recurrence. Telomerase activity, a hallmark of cancer characterized by overcoming the replicative senescence, is upregulated in over 90% of patients with UC. Somatic mutations in the promoter region of telomerase reverse transcriptase (TERT) are frequently detected in UC, and drive telomerase activity. Recent studies have demonstrated a strong association between TERT promoter mutation and tumorigenesis of UC. Also, TERT promoter mutation has great potential for diagnosis as well as prognosis in UC treatment, and this is also applicable for the liquid biopsy techniques. In this review, we discuss the progress in these areas and highlight the challenges, clinical potential, and future direction for developing UC treatment methods.